Analyzing Cultivated Land Protection Behavior From the Perspective of Land Fragmentation and Farmland Transfer: Evidence From Farmers in Rural China - Lu, Hua; Chen, Yijing; Huan, Haoting; Duan, Na (Frontiers in Environmental Science, 2022)
Cultivated land protection is an important way to mitigate land pollution and realize the sustainable development of agriculture. To reveal the key factors influencing farmers' behavior of adopting cultivated land protection techniques (FBACT) from the perspective of land fragmentation and farmland transfer and to analyze the differences, a multivariate probit model is adopted to quantitatively analyze the impacts on FBACT based on field research and questionnaire surveys conducted in Jiangsu Province, China. The results show that farmland transfer promotes FBACT and that large areas of transfer-in land encourage it. Transfer-in land from outside villages reduces FBACT. The willingness of farmers to adopt protection techniques is affected by their age, their education level, family labor and the agricultural labor price, and it is hindered by land fragmentation. Encouraging farmers to transfer-in land from local villages and increasing their expectations of benefits from cultivated land protection will inspire them to adopt protection techniques. To increase the farmland transfer rate and to alleviate land fragmentation, the government should enhance the management of farmland transfer contracts and strengthen the stability of farmland use rights in farmland transfer. Promoting the transfer and integration of adjacent plots and appropriately expanding plot size will help improve FBACT.